A genomic search for linkage of neurofibromatosis to RFLPs. Issue 9 (September 1987) - Barker, D; Wright, E; Nguyen, K; Cannon, L; Fain, P; Goldgar, D; Bishop, D T; Carey, J; Kivlin, J; Willard, H
Abstract : Our initial attempt to map NF was directed towards chromosomes 4 and 19, both of which had provided positive evidence for linkage in previous reports. This analysis showed no evidence in support of either hypothesis. Our second attempt at mapping NF was a general search of the genome, analysing a set of markers selected according to their degree of polymorphism, chromosomal location, ease of use, and availability. Data for linkage analysis were obtained from 17 multiplex families which are segregating a gene for NF. Linkage analyses were performed using PAP. Of note is the lod score of +1.17 at a recombination fraction of 0.1 between NF and the centromere of chromosome 17.